Interpretacja Międzynarodowego paktu praw obywatelskich i politycznych w świetle raportów Komitetu Praw Człowieka - Michalska, Anna (Wydział Prawa i Administracji UAM, 1986)
Three important anniversaries are to be observed in the international activity in the field of the protection of Human Rights in 1986. It was 20 years ago when the General Assembly adopted International Covenants on Human Rights. 10 years ago those international instruments entered into force. 10 years have passed since the Committee on Human Rights was created, it excercises control upon implementation of the Covenant on Civil and Political Rights. These aniversaries stem reflections and analyses. The subject matter of the article is the interpretation of provisions of the Covenant performed by the Committee in the pro-cess of studying reports of the States Parties. The article was prepared mostly on the basis of the annual reports submitted to the General Assembly by the Committee, The article consists of three parts. The first one discusses competence bestowed upon the Committee by the Covenant and Optional Protocol. This information is intend ed to serve as a kind of introduction to the further deliberations. The second part presents the forms in which the Committee can express its views and opinions. It is the case of general comments and of discussions in the process of studying reports of States Parties., In the first instance we have to deal with a position of the Committee, while in the second with the opinions and views of its particular members. In the third part the authoress analyses main directions in interpretation of the general clauses (art. 1-4 of the Covenant) and of some provisions formulating the catalog of human rights (part III of the Covenant). In the opinion of the authoress, the Committee's interpretation is sometimes exceeding the verbal meaning of the Covenant provisions. The interpretation of the right to life can serve here as an example. The Committee has exhibited here an ouvert tendency of law making which was met with reservations of some of its members. The authoress on her part does not attempt at evaluating the efectiveness of the international control system, based on reports of States Parties to the Committee. Yet she is advocating the opinion that considerations of the Committee can contribute to unifying implementation of Human Rights by States. In spite of the fact that these considerations are not legally binding for those States.
Interpretation of the international Convenant on civil and political rights in the light of reports of the Human Rights Committee